Full Torus Electromagnetic Gyrokinetic Particle Simulations with Kinetic Electrons (Communications in Computational Physics, 2018)
The full torus electromagnetic gyrokinetic particle simulations using the hybrid model with kinetic electrons in the presence of magnetic shear is presented. The fluid-kinetic electron hybrid model employed in this paper improves numerical properties by removing the tearing mode, meanwhile, preserves both linear and nonlinear wave-particle resonances of electrons with Alfven wave and ion acoustic wave.